Some combinatorial invariants related to a cryptosystem - Brincatt, Karl; Piper, Fred; Wild, Peter (Utilitas Mathematica, 2006)
We count the number of distinct strings that arise when β random bits are interspersed between the bits of a string x of length α and weight . We show that this number is independent of x and of the weight w. This leads to a combinatorial identity and has application in cryptography to the design of Randomized Cryptosystems.